Links of interest of Swiss MPs: a comprehensive dataset - Martin Péclat; Stefano Puddu (University of Neuchâtel, Institute of Economic Research (IRENE), 2015)
This study provides a comprehensive, accurate and ready-to-use dataset on the relationships between the members of the Swiss Parliament and groups of interests. We capture politicians' linkages exploiting (1) their mandates in legal entities; (2) the enterprises, associations or other organizations related to the people they invite for attending parliamentary sessions; and (3) their occupations. Using NOGA 2008 and SSCO 2000 codes, legal entities and professions are classified into 28 categories. We approximate politicians' ties intensity by the number of occurrences in a particular category. The results show that there are substantial differences between the two chambers, and across the main parliamentary groups. The three types of information employed provide complementary information.
Keywords: D7; H7; 330; Groups of pressure; lobbies; special interests; Swiss Parliament; voting behaviour